Personalization vs. Privacy: Balancing Data-Driven Marketing and Consumer Trust in the Digital Economy - Hidayat, Ahmad Syarif; Mardani, Himawan Pramulanto, Agnes Dini (YUME : Journal of Management, 2025)
This study explores the intricate relationship between personalization in digital marketing, privacy concerns, perceived data transparency, and consumer trust in the context of the digital economy. Employing a qualitative research design integrated with Smart PLS analysis, the research examines how transparency mediates the effects of personalization and privacy perceptions on consumer trust. Findings indicate that personalization has a significant positive effect on consumer trust, particularly when perceived data transparency is high. Conversely, privacy concerns negatively influence transparency perceptions, which in turn diminish trust. The mediating role of transparency is found to be crucial in balancing consumer desires for personalized experiences with their need for privacy assurance. These results contribute to the theoretical discourse on the personalization–privacy paradox and offer practical insights for businesses and policymakers seeking to build sustainable, trust-based relationships with consumers in data-driven environments. Keywords: Personalization, Privacy Concerns, Data Transparency, Consumer Trust, Digital Marketing